The effects of maternal depression on their perception of emotional and behavioral problems of their internationally adopted children - Krista Liskola; Hanna Raaska; Helena Lapinleimu; Jari Lipsanen; Jari Sinkkonen; Marko Elovainio (BMC, 2021)
Abstract Background Even though child psychopathology assessment guidelines emphasize comprehensive multi-method, multimodal, and multi-informant methodologies, maternal-report symptom-rating scales often serve as the predominant source of information. Research has shown that parental mood symptomatology affects their reports of their offspring's psychopathology. For example, the depression-distortion hypothesis suggests that maternal depression promotes a negative bias in mothers' perceptions of their children's behavioral and emotional problems. We investigated this difference of perception between adoptive mothers and internationally adopted children. Most previous studies suffer from the potential bias caused by the fact that parents and children share genetic risks. Methods Data were derived from the Finnish Adoption (FinAdo) survey study (a subsample of adopted children aged between 9 and 12 years, n = 222). The Child Behavior Checklist (CBCL) was used to assess emotional and behavioral problems and competences of the adopted children. The CBCL was filled in by the adopted children and the adoptive mothers, respectively. Maternal depressive symptoms were measured using the short version of the General Health Questionnaire. Results On average, mothers reported less total CBCL symptoms in their children than the children themselves (0.25 vs 0.38, p-value < 0.01 for difference). Mothers' depressive symptoms moderated the discrepancy in reporting internalizing symptoms (β = − 0.14 and p-value 0.01 for interaction) and the total symptoms scores (β = − 0.22 and p-value < 0.001 for interaction) and externalizing symptoms in girls in the CBCL. Limitations The major limitation of our study is its cross-sectional design and the fact that we only collected data in the form of questionnaires. Conclusions The results of our research support the depression-distortion hypothesis concerning the association of maternal depressive symptoms and child internalizing symptoms and externalizing symptoms in girls in a sample without genetic bias